'I didn't even know it was a thing': Australian young adults' experience of economic abuse. (11th November 2022) - Kutin, Jozica Johanna; Russell, Roslyn; Reid, Mike
Summary: Economic abuse is a form of intimate partner violence that involves one partner controlling or restricting, exploiting or sabotaging the economic resources of the other partner. Little is known how economic abuse manifests in young people's relationships or how to prevent it. This study explored young adults' experiences of economic abuse and identified the factors associated with economic abuse in their relationships. Twenty-four young adults (18 women and 6 men) aged 18–29, were interviewed in-depth using both unstructured narrative and semi-structured interview questions. Thematic analysis was used to identify forms of economic abuse. Common experiences of economic abuse included: exploitation of financial and other resources, controlling access to money, damage to property and sabotage of employment and study. The contextual factors included lack of awareness of economic abuse, valuing love and relationships over money and fear of conflict and rejection. We argue that economic abuse prevention strategies should target young adults in their relationship formation stage and take into account the context of relationships and the issues young people face when venturing into cohabitation.